244 GENDER DIFFERENCE IN ALDOSTERONE EXCRETION IN SUBJECTS WITH RESISTANT HYPERTENSION. (1st January 2006) - Gaddam, K. K.; Pratt-Ubunama, M. N.; Nishizaka, M. K.; Calhoun, D. A.
Abstract : Background: We have recently reported a 20% incidence of primary aldosteronism (PA) among subjects with resistant hypertension. The reason for the high prevalence of hyperaldosteronism in this high-risk group is unknown. The current study was designed to identify potential stimuli of aldosterone secretion in subjects with resistant hypertension. Methods: Consecutive subjects referred to the University of Alabama at Birmingham (UAB) hypertension clinic for resistant hypertension (uncontrolled blood pressure on 3 antihypertensive agents) were prospectively evaluated with a plasma aldosterone concentration (PAC), plasma direct renin (PDR), a 24-hr urine collection for aldosterone, cortisol, sodium, and potassium during a normal diet. All subjects were on a stable antihypertensive regimen without use of potassium-sparing diuretics. Results: A total of 85 subjects were evaluated, including 42 males and 43 females. Age (53.9 6 11.4 vs 54.8 6 12), BMI (32.6 6 5.4 vs 32.8 6 7.5), clinic blood pressure (153 6 28/91 6 17 vs 158 6 26/85 6 15), number of antihypertensive medications (4.0 6 1.2 vs 4.3 6 1) were similar in male and female subjects. Urinary aldosterone was higher in men compared to women (13.3 6 7.4 vs 8.9 6 4.9 μg/24 hr, p = .0019). Urinary cortisol (l09.1 6 43.4 vs 71 6 45.1 μg/24 hr, p = .0002), sodium (231.5 6 115.7 vs 160.5 6 87.6 mEq/24 hr, p = .0021), and potassium (77.4 6 30.3 vs 59.9 6 24.6 mEq/24 hr, p ≤ .0001) were also higher in male subjects. Urinary aldosterone excretion was positively correlated with cortisol excretion (see the Figure). Conclusion: These data are the first to demonstrate a gender difference in aldosterone excretion in subjects with resistant hypertension. Potential stimuli of aldosterone underlying this gender difference include greater dietary ingestion of potassium by the male subjects and/or ACTH stimulation as suggested by the same gender difference in aldosterone and cortisol excretion.